Aperiodic EEG signatures: unveiling the interplay between APOE ε4 and mild cognitive impairment subtypes - Eyamu, Joel; Ku, Boncho; Kim, Kahye; Lee, Kun Ho; Kim, Jaeuk U. (Frontiers in Aging Neuroscience, 2026)
BackgroundMild cognitive impairment (MCI) is a cognitive decline syndrome in the elderly, often a precursor to dementia. It is a heterogeneous condition that can signal degenerative disorders like Alzheimer’s or non-degenerative conditions such as vascular issues, depression, or poorly managed diabetes. Early detection of MCI is crucial for timely intervention, and differentiating its phenotypes helps in understanding its causes, progression, and treatment. EEG, which records brain electrical activity, consists of rhythmic and arrhythmic components. Examining these inherently overlapping EEG components calls for quantification, ensuring that an appropriate physiological mechanism is attributed to a given neural response. This study explores the interaction between APOE ε4 (APOE4) and cognitive impairment on non-oscillatory EEG activity.MethodsWe examined aperiodic EEG activity using a parameterized spectral estimation approach in a sample comprising 751, 142, and 279 cognitively normal (CN), non-amnestic (naMCI), and amnestic (aMCI) MCI patients, respectively. The 5-min EEG was recorded using a prefrontal two-channel EEG device in a resting state, eyes closed. Cognitive decline was assessed using the Seoul Neuropsychological Screening Battery (SNSB) and the Mini-Mental State Examination (MMSE). The analyses were performed using various statistical methods, including independent t-tests and generalized linear models (GLM) with an identity link function. These analyses investigated the main and interaction effects of the APOE4 status and participants’ cognitive states.ResultsWe found interactions between APOE4 and cognitive states in the aperiodic EEG exponent and the spectral power ratio (SPR). Distinct patterns were observed in the exponent, offset, and SPR between APOE4 non-carriers and carriers across the CN, naMCI, and aMCI. Among the APOE4 carriers, the aMCI individuals exhibited heightened aperiodic activity and a reduced SPR than the naMCI. Furthermore, the CN had a lower SPR compared to the naMCI. However, no differences in the aperiodic component and SPR were observed in the APOE4 non-carriers across the cognitive states.DiscussionThe higher aperiodic component and a reduced SPR observed in aMCI relative to naMCI in APOE4 carriers may indicate an interplay between genetic predisposition, neuropathological changes, and cognitive decline. These aperiodic components, combined with APOE4 status, represent promising neurophysiological markers that may help identify individuals at elevated risk for cognitive decline or progression toward AD.